Innovative approaches to optimizing taxation in organizations - E. A. Kirova; E. A. Ponomarenko (Вестник университета)
In conditions of rapid progress in technology and constant changes in tax legislation, the task of optimizing the taxation in organizations is becoming increasingly difficult for business entities. The use of innovative approaches in the process allows to increase efficiency and reduce tax expenses. In addition, innovative methods and technologies implementation can reduce time for tax optimization, simplify tax reporting monitoring and analysis, and improve decisions quality. The purpose of the study is to find innovative approaches to optimize taxation in organizations. The following tasks have been set: to classify the types of tax risks; to assess tax risks on the basis of determining the tax burden of organizations; to form innovative approaches to optimize taxation in organizations. As a result of the conducted research on the example of Technoprom the organizations are offered to determine the tax burden and forecast its dynamics in the future, as well as to apply innovative approaches to optimize taxation on the basis of artificial intelligence through the use of methods of automating tax accounting and reporting and blockchain technology. System approach, analysis and synthesis, as well as the method of expert evaluations method have been applied as the research methods.